Implementation of Intelligent Distributed Feeder Automation for Distribution Network. (July 2020) - Wu, Linwei; Huang, Yibiao; Li, Rong; Xie, Xicheng; Wang, Yifan
Abstract: With the increasing demand for power supply reliability in the society, the demand for the degree of feeder automation in the distribution network is also increasing, and the feeder automation function for the purpose of improving power supply reliability is gradually improving. The research and judgment strategy of fault section location, isolation and non-fault section power supply recovery based on the feeder automation function has become a research hotspot. This paper introduces the research and judgment strategy of fault information interaction based on communication network for fast location and isolation of fault section, and expounds the research and judgment strategy of intelligent distributed feeder automation of boundary switch and contact switch in main line and branch line of distribution network in detail.